Efisiensi Program Unggulan (Tahfidh, Kitab dan Bahasa) di Pondok Pesantren Salafiyah Hamalatul Qur'an Jogoroto Jombang - Muhammad Lubis Abdillah; Wahyudi Wahyudi (Lembaga Yasin AlSys, 2026)
This study was motivated by the importance of efficiency in the implementation of the flagship programs Tahfidh, Kitab, and Language at Pondok Pesantren Salafiyah Hamalatul Qur’an Jogoroto Jombang as an effort to produce high-quality and competitive santri in the modern era. The study aimed to analyze the level of efficiency in program implementation, identify supporting and inhibiting factors, and examine the quality of learning, the intensity of activities, the appropriateness of learning levels, and the structured use of time. A qualitative approach was employed through observation, in-depth interviews, and document analysis. The findings indicate that the flagship programs of Tahfidh, Kitab, and Language run relatively efficiently, supported by a well-planned curriculum, students’ discipline, and effective time management. Nevertheless, implementation efficiency remains constrained by the limited number of teaching staff and supporting facilities. The study concludes that, although program efficiency has generally been achieved, improving both the quality and quantity of resources is still urgently needed to ensure the sustainability and continuous enhancement of program quality. The implications of this research provide an empirical basis for the evaluation and further development of the pesantren’s flagship programs.